IMPLEMENTASI NILAI-NILAI PENDIDIKAN AKHLAK DALAM KITAB IHYA’ ULUMUDDIN KARYA IMAM AL-GHAZALI DI PONDOK PESANTREN ASSUNIYAH KENCONG-JEMBER-JAWA TIMUR - Muhsin, Hafidul; Imaduddin (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2022)
Islamic boarding schools are educational institutions that provide maximum and in-depth religious learning. Islamic boarding schools have their own uniqueness in fostering their students, namely the independent attitude of various parties including the government. Islamic boarding schools stand and develop from the community so that they have freedom in providing educational regulations and are not bound by standard government regulations. Islamic boarding schools have characteristics that do not change with the times and technology. Islamic boarding schools are one of the moral development institutions. Islamic boarding school education increases religious knowledge and moral formation and teaches the character of honesty to prepare students for a simple life with a heart that is clean from reprehensible traits. The role of the kiai in moral formation is very crucial among the different character backgrounds of the santri. The role of the kiai is through exemplary, habituation of discipline which is enforced as a rule in Islamic boarding schools. The focus of this research is to find out the concept of reciting the Ihya' Ulumuddin Book by Imam Al-Ghazali at the Assuniyah Kencong Jember Islamic Boarding School, the implementation of moral education values based on the thoughts of Imam Al-Ghazali in the Ihya' 'Ulumuddin book and the learning model for the Ihya' 'Ulumuddin book in Assuniyah Kencong Jember Islamic boarding school. This study uses a qualitative approach, emphasizing its analysis on the comparative inference process of the dynamics of the phenomena relationship using scientific logic. The result of this research is the recitation of the Ihya' book, the method used is the bandongan method and lectures from the kiyai. Activities carried out in Islamic boarding schools are activities related to religious activities, students are limited to the environment outside the Islamic boarding school. This research has conceptual findings with the NIAT model which stands for Nurut, Istiqomah, Actualization, Tawaduk.